2014
DOI: 10.1016/j.dcn.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Default Mode and Central Executive Networks across early adolescence: A longitudinal study

Abstract: The mature brain is organized into distinct neural networks defined by regions demonstrating correlated activity during task performance as well as rest. While research has begun to examine differences in these networks between children and adults, little is known about developmental changes during early adolescence. Using functional Magnetic Resonance Imaging (fMRI), we examined the Default Mode Network (DMN) and the Central Executive Network (CEN) at ages 10 and 13 in a longitudinal sample of 45 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
233
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 280 publications
(281 citation statements)
references
References 75 publications
44
233
3
1
Order By: Relevance
“…Andrews-Hanna et al identified these seeds in a young adult sample. While there is evidence that long-range connectivity within the DMN continues to develop well into adolescence, by adolescence these changes are limited to increases in functional connectivity between nodes, with all major DMN nodes fully formed in childhood 55,56 . Therefore, we felt justified in using these seeds in an adolescent population.…”
Section: Regions Of Interest (Rois)mentioning
confidence: 99%
See 1 more Smart Citation
“…Andrews-Hanna et al identified these seeds in a young adult sample. While there is evidence that long-range connectivity within the DMN continues to develop well into adolescence, by adolescence these changes are limited to increases in functional connectivity between nodes, with all major DMN nodes fully formed in childhood 55,56 . Therefore, we felt justified in using these seeds in an adolescent population.…”
Section: Regions Of Interest (Rois)mentioning
confidence: 99%
“…It was also important to control for age and IQ, given that development of the DMN continues well into adolescence 56 and intelligence has been associated with connectivity strength 58 . Results are reported at a threshold of p<.05 (two-tailed), false discovery rate (FDR) correction at the level of the entire analysis (i.e., controlling for each seed and each target seed simultaneously).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Research suggests that the brain has two fundamental processes: one of pruning in early adolescence, the other of myelin formation in middle to late adolescence (e.g., Sherman et al, 2014). Pruning enables regions of the brain to become more differentiated; myelin enables these remaining regions to become more linked and integrated.…”
Section: Adolescencementioning
confidence: 99%
“…For instance, performance on a simple planning task, such as the three-disc Towers of Hanoi task, is already equal to adult performance by six years of age, but performance on tasks involving the implementation of sorting strategies do not reach an adult level until the age of ten (Welsh, Pennington, & Groisser, 1991). Recent research has shown not only that physical changes during childhood involve the strengthening of the neural network within certain areas but also that the network connecting different brain areas weakens (Sherman et al, 2014). Individual differences among children in brain maturation have been hown to be closely related to differences in intellectual functioning (Koenis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%